Exploring the experiences of South African youth living with myasthenia gravis - Gebashe, Nomfundo Zime Nokulunga (Department of Social Development, 2025)
This study explored experiences of South African youth living with Myasthenia Gravis (MG). Myasthenia gravis is a rare autoimmune disease marked by skeletal muscle weakness caused by the breakdown of communication between nerves and muscles at the neuromuscular junction. The aim was to understand how MG affects emotional and physical well-being, social and family relationships as well as educational and employment prospects of young people who have been diagnosed with the disease. In addition, the study sought to understand the role of culture and religion on how youth understand and cope with MG. Using a qualitative research design and a purposive sampling technique, eight young people from diverse backgrounds who were receiving MG treatment at Groote Schuur Hospital (GSH) in Cape Town were interviewed about their experiences of living with MG. Data collection took place through in-person interviews which were conducted at the MG clinic located within the neurology division at GSH. A semi-structured interview guide was used as a data collection instrument. Data was analysed through Applied Thematic Analysis (ATA). Findings from the study indicate that a shortage of specialist doctors, poor awareness and lack of accountability among Health Care professionals (HCPs), especially those in township communities where most participants were from, added to participant experiences of symptom progression and delayed diagnoses. Findings also suggest that MG may mentally affect youth's personal relationships as well as spousal relationships in instances where participants were married. The research concludes that skills and knowledge gaps in public institutions led to delayed diagnoses allowing, patients' symptoms to progress while awaiting diagnoses. In contrast, services at private hospitals showed better outcomes. It is also concluded that public awareness of MG and HCPs accow1tability is crucial to enhance patients' health prospects and ability to cope with MG. The study recommends that patient referral procedures be better regulated with mandated time frames for HCPs to refer patients if they struggle to make a correct diagnosis. This is to reduce the occurrence of delayed diagnoses observed amongst the youth diagnosed with MG. Furthermore, provision of financial aid and grants to support youth, especially students with disabilities who are unable to study full-time or in-person are recommended.